Psychological morbidity, social support, and relationship intimacy in pregnant Portuguese women - Costa, Eleonora C. V. (2017)
Pregnancy can predispose women to stress and depression, with social support and intimacy being protective factors for the development of these disorders. This study evaluated the relationship between stress (various stressors), social support, intimacy and depression in a sample of 169 pregnant women attending the Childbirth Preparation classes. Depressive mood was positively correlated with both stress and satisfaction with social support and intimacy were negatively correlated with stress and depressive. In short, it is pertinent to create networks of support and intervention in stress for the promotion of mental health of pregnant women.